222k views
5 votes
Y+5=-2(x-3)
convert to slope intercept form, and standard form.
show work​

User Mario Ene
by
5.5k points

1 Answer

4 votes

Answer:

Slope intercept form: y = -2x +1

Standard form: 2x +y = 1

Explanation:

Slope intercept form: y =mx +b

Here, m is the slope and b is the y-intercept.

y + 5 = -2(x -3)

y +5 = -2x + 6

y = -2x + 6 - 5


\sf \boxed{\bf y = -2x + 1 }

Standard form: Ax + By = C

y = -2x + 1


\sf \boxed{2x +y = 1}

User Vcxz
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.